TRADISI MANJOPUIK LIMAU DI SEBERANG PANTAI KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI - Nindy Yulia Ningsih; Dudung burhanudin; Syafrial Syafrial (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is the traditon of manjopuik limau across the coast of Kuantan district of Kuantan Mudik district of Singingi. The purpose of this study is to describe how the tradition of manjopuik limau across te coast Kuantan district mudik Kuantan Singingi district, and how the aesthetics of language un the manjopuik tradition of limes across the coast of Kuantan sub-district queue mudik district Singingi. this type of research is descriptive qualitative research and ethnography approach that try to tell the existing problem solving based on existing facts. The results of this study is a narrative descriptive that is comprehensive along with interpretations that interpret all aspects of culture. This research tries to get as comlete information as possible anout the manjopuik tradition of limes across the coast of Kuantan Mudik district Singingi. the data in this research are verbal, nonverbal and aesthetic data of language contained in the manjopuik tradition of limes. Validity of data obtained by triangulation technique. Then the data are analyzed and classified according to the stage of the manjopuik tradition of limes. The result of research, found verbal elements, nonverbal elements, and language aesthetics in the tradition of manjopuik limau amounted to eighty nine data. The division of data is (1) verbal elements amounted to twenty data,(2) nonverbal elements of eight data, and (3) aesthetic language totaled sixty on data.Keywords: Traditions of manjopuik limau, Seberang Pantai, Kuantan Mudik, Kuantan Singingi.